2020
DOI: 10.1093/scan/nsaa152
|View full text |Cite
|
Sign up to set email alerts
|

The influence of prior intention on joint action: an fNIRS-based hyperscanning study

Abstract: Motor performances of the same action are affected by prior intentions to move unintentionally, cooperatively or competitively. Here, a back-and-forth movement task combined with a motion capture system and functional near-infrared spectroscopy (fNIRS)-based hyperscanning technology was utilized to record both the behavioral and neural data of 18 dyads of participants acting in pairs [joint conditions: no-intention, cooperative (Coop) and competitive (Comp)] or alone (single conditions: self-paced and fast-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…This will need to be verified on a moving-base flight simulator in the future, since this experiment used a fixed-based flight simulator. BA6 is thought to play an important role in complex and coordinated motor planning ( 31 ). Similar to BA1, our results indicated that BA6 was more active in AHRS- than in RH ENG failure, whereas Yamauchi et al found that the hemodynamic changes in BA6 rose significantly in a linear trend with the increase in workload ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…This will need to be verified on a moving-base flight simulator in the future, since this experiment used a fixed-based flight simulator. BA6 is thought to play an important role in complex and coordinated motor planning ( 31 ). Similar to BA1, our results indicated that BA6 was more active in AHRS- than in RH ENG failure, whereas Yamauchi et al found that the hemodynamic changes in BA6 rose significantly in a linear trend with the increase in workload ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…One previous fNIRS study has measured activity differences in competitive and cooperative motor movement tasks. Chen et al ( 2020 ) showed increased activation for social brain regions in competition and cooperation with greater increases in competitive conditions. Finally, to clarify the function of these social brain regions, we chose to use an activity-based rather than synchrony-based analysis.…”
Section: Introductionmentioning
confidence: 99%